Discrete and polymeric organometallic-organic assemblies based on the diarsene complex [(Cp)2Mo2(CO)4(μ, η2-As2)], AgPF6 and N-donor organic molecules. (20th January 2021) - Moussa, Mehdi Elsayed; Schiller, Jana; Seidl, Michael; Shelyganov, Pavel A.; Scheer, Manfred
Abstract : The first mixed-ligand self-assembly reactions of the diarsene complex [Cp2 Mo2 (CO)4 (μ, η 2 -As2 )] and N-donor organic molecules in the presence of AgPF6  allow for the synthesis of two discrete and four polymeric supramolecular aggregates. Abstract : Three-component reactions of the organometallic diarsene complex [Cp2 Mo2 (CO)4 (μ, η 2 -As2 )] (B) (Cp = C5 H5 ) with AgPF6 in the presence of different N-donor linkers are presented. Depending on the organic linker used, discrete [{(η 2 -B)2 Ag}2 (L1)][PF6 ]2 (1) and [{(η 2 -B)2 Ag}2 (L2)][PF6 ]2 (2) organometallic-organic hybrid assemblies and polymeric [{(η 2 -B)Ag}(L3)] n [PF6 ] n (3), [{(η 1 :η 2 -B)2 (CH3 CN)2 Ag2 }(L4)] n [PF6 ]2 n (4), [{(η 1 :η 2 -B)2 (CH3 CN)2 Ag2 }(L5)] n [PF6 ]2 n (5) and [{(η 1 :η 2 -B)2 (η 1 :η 1 -B)Ag2 }(L5)] n [PF6 ]2 n (6) ones are obtained. 4–6 possess unique structures in which Ag⋯Ag interactions occur.